Determinants of innovative behavior from the perspective of individual factors: A conceptual framework - Corzo Morales, Yesica Xiomara; Contreras Pacheco, Orlando Enrique (Intangible capital, 2024)
Purpose: This study outlines the structured dimensions of innovative work behavior (IWB). It interprets and associates the underlying characteristics found in the existing literature to develop a conceptual framework, which provides a comprehensive overview of IWB from the perspective of individual factors. This study also identifies the cognitive and behavioral determinants of individual innovative behavior and the most related management theories. Furthermore, it investigates the quantitative modeling methods used to explore this phenomenon and recommends practical managerial applications to promote employees’ innovative behavior.  Design/methodology/approach: The conceptual framework was developed through a systematic literature review, following three fundamental stages: 1) planning, 2) development, and 3) synthesis of the review. We retrieved 637 documents, spanning a 5-year time frame, from both Scopus and Web of Science academic information indexing and retrieval systems. Subsequently, seven inclusion and exclusion criteria were applied to determine the eligibility of the studies, incorporating the guidelines from the PRISMA statement. The final sample consisted of 49 scientific articles that answered five guiding questions, leading to the integration of the framework.  Findings: This study examines the dimensions of IWB—that is, the generation, introduction, and realization of ideas—by analyzing the fundamental properties mentioned by the authors of the selected documentary sample. It further identifies 48 determinants of IWB, categorized under three organizational management theories: personality traits, self-determination, and social exchange theories. This study also analyzes the applied quantitative research methods, business sectors, and countries investigated, identifying the most commonly used methods and most frequently investigated sectors and countries. Additionally, it highlights the current research agenda for promoting IWB as an enabler of competitive organizational development. Finally, we present a conceptual framework that provides a theoretical structure for understanding individual IWB.  Practical implications: We clarify the current research landscape of IWB in an organizational context. We also help identify the level of academic interest in this subject for future studies. Furthermore, we compile valuable recommendations for business managers aiming to enhance the competencies of their workforce in managing innovative processes.  Originality/value: We introduce a new conceptual framework for IWB that considers its primary strategic purposes. Therefore, this study is a reference point for future empirical innovation management studies. It provides a classification of individual-level determinants with a cognitive and behavioral focus, incorporating constructs such as spirituality, altruism, ethical and empathic behaviors, and resilience.